Changes in preterm birth and caesarean deliveries in the United States during the SARS‐CoV‐2 pandemic. Issue 4 (13th September 2021) - Gemmill, Alison; Casey, Joan A.; Catalano, Ralph; Karasek, Deborah; Margerison, Claire E.; Bruckner, Tim
Abstract: Background: Preliminary studies suggest that the SARS‐CoV‐2 pandemic and associated social, economic and clinical disruptions have affected pregnancy decision‐making and outcomes. Whilst a few US‐based studies have examined regional changes in birth outcomes during the pandemic's first months, much remains unknown of how the pandemic impacted perinatal health indicators at the national‐level throughout 2020, including during the 'second wave' of infections that occurred later in the year. Objectives: To describe changes in monthly rates of perinatal health indicators during the 2020 pandemic for the entire US. Methods: For the years 2015 to 2020, we obtained national monthly rates (per 100 births) for four perinatal indicators: preterm (<37 weeks' gestation), early preterm (<34 weeks' gestation), late preterm (34–36 weeks' gestation) and caesarean delivery. We used an interrupted time‐series approach to compare the outcomes observed after the pandemic began (March 2020) to those expected had the pandemic not occurred for March through December of 2020. Results: Observed rates of preterm birth fell below expectation across several months of the 2020 pandemic. These declines were largest in magnitude in early and late 2020, with a 5%–6% relative difference between observed and expected occurring in March and November. For example, in March 2020, the observed preterm birth rate of 9.8 per 100 live births fell below the 95% prediction interval (PI) of the rate predicted from history, which was 10.5 preterm births per 100 live births (95% PI 10.2, 10.7). We detected no changes from expectation in the rate of caesarean deliveries. Conclusions: Our findings provide nationwide evidence of unexpected reductions in preterm delivery during the 2020 SARS‐CoV‐2 pandemic in the US. Observed declines below expectation were differed by both timing of delivery and birth month, suggesting that several mechanisms, which require further study, may explain these patterns.